(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2018)
Al Hafiz Maghlatay has been known of his numerous resources in his book “Footnoting to Explanation of the Sahih Compilation”. They were shaping a diversity of sciences. Thus, this research has primarily been dedicated to these scattered resources trying to organize and introduce them. This research paper aims to investigate the resources in the book and categorize them according to their themes, as if they were in a book of explanation or Hadith issues, or editions and additions, or Fiqh or else. Each issue requires a specific part and these resources were categorized based on their writers’ death. The research came up with a fact showing the importance of the book “Footnoting” between the explanations of Bukhari in terms of the numerous resources of their authors, which made his explanation stood out. This is in addition to the wide knowledge of the author and his revision, and knowledge of books, and the benefit he got from them in his writings.